Photocatalytic activity of TiO2 based composite films by porous conjugated polymer coating of nanoparticles. (February 2016) - Song, Y.; Zhang, J.; Yang, L.; Cao, S.; Yang, H.; Zhang, J.; Jiang, L.; Dan, Y.; Le Rendu, P.; Nguyen, T.P.
Abstract: To improve the photocatalytic activity of titanium dioxide (TiO2 ), one possible approach consists of extending light absorption to visible range by using conjugated polymers together with TiO2 nanoparticles in order to enhance light harvesting. The use of appropriate polymers would facilitate the charge separation at the contact surface of the materials and hence effectively increases the photocatalytic reaction, allowing a more efficient oxidation of organic pollutants. In this work, we proposed an improved synthesis method for obtaining conjugated polymer/TiO2 composite thin films having a porous morphology, which can potentially increase the contact surface between materials. A polyvinyl alcohol/titanium dioxide (PVA/TiO2 ) precursor was prepared and deposited as thin films on glass substrates. The films were then thermally treated by a controlled protocol, resulting in the transformation of PVA into a conjugated polymer coating the TiO2 particles. The morphology of the obtained composite films showed a porous aspect indicating that the polymer and the nanoparticles were intimately mixed. Photocatalytic activities of the porous composite films (P-PVA/TiO2 ) were examined through the degradation processes of a phenol solution under visible light irradiation. The results showed that, by their particular morphology, which increased the polymer-nanoparticle contact surface, P-PVA/TiO2 composites easily and efficiently degraded phenol under visible light.